Human internal and external exposure to synthetic musks in China - Xue Zhang; Xu Wan; Jianhui Zhao; Xiaohua Guo; Zhenxin Wang; Zishan Diao; Wenpeng Li; Yameng Zhao; Xirui Zhao; Weijia Wang; Xiaohan Zhang; Shuguang Wang; et al. (Ecotoxicology and Environmental Safety)
The widespread utilization of synthetic musks (SMs) in various consumer and personal care products (PCPs) has led to human external exposure through dermal absorption, inhalation of volatile fragrances, and ingestion of contaminated foods, dust, and liquids. Nonetheless, investigations comparing external and internal exposures in humans remain limited in China, particularly regarding internal exposure assessments in blood, which have lacked follow-up over the past decade. In this study, data concerning the concentrations of SMs in 135 blood samples (68 females and 67 males) obtained from residents of Shanghai are provided, representing the sole publication within the last decade on this topic. The findings suggest a potential association between SM concentrations in females and their income and ages. Additionally, the concentrations in blood are higher than in urine, suggesting that relying solely on urine assessments may underestimate health risks associated with internal exposure. Furthermore, data on internal exposure in human fluids reveal SMs' potential transfer to infants via breast milk, posing substantial threat. Noteworthy, we quantify total external exposure across various pathways for Chinese population. Our findings indicate that PCPs are identified as the predominant source of external exposure for adolescents and adults. However, in the case of infants and children, food ingestion, and PCPs dermal absorption make substantial contributions, representing 80.53 % and 16.06 % of the total for infants, and 69.96 % and 22.40 % for children, respectively. Notably, the total estimated daily intake (EDI), derived from urine analysis, falls notably below the total external exposure. While the contribution of each SM exhibits considerable variability, which can be ascribed to the distinct metabolic pathways of these compounds in vivo. Hence, additional research on the metabolism and transformation of SMs in humans is urgently needed for better human health risk assessment in the future.